2018
DOI: 10.1007/s10519-018-9903-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Functioning in Patients with 22q11.2 Deletion Syndrome: A Meta-Analytic Review

Abstract: The 22q11.2 deletion syndrome (22q11.2DS) is a known risk factor for development of schizophrenia and is characterized by a complex neuropsychological profile. To date, a quantitative meta-analysis examining cognitive functioning in 22q11.2DS has not been conducted. A systematic review of cross-sectional studies comparing neuropsychological performance of individuals with 22q11.2DS with age-matched healthy typically developing and sibling comparison subjects was carried out. Potential moderators were analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Multimorbid presentation of neurodevelopmental and psychiatric conditions is common (9)(10)(11)(12). All RGDs studied to date affect cognition to varying degrees and affect a broad range of cognitive functions, including reaction time, attention, executive functions, and social cognition (13,14). Early studies highlighted distinctive behavioral profiles, such as social disinhibition, excessive empathy, and non-social anxiety described in 7q11.23 deletions (Williams-Beuren syndrome (15)); insatiable appetite in paternal 15q11.2-q13 deletions (Prader-Willi syndrome (16)); sleep disturbances in 17p11.2 deletions (Smith Magenis syndrome) (17); as well as childhood apraxia of speech in 16p11.2 proximal deletions (18).…”
Section: Do Rare Variants Exert Specific or Shared Effects On Psychop...mentioning
confidence: 99%
“…Multimorbid presentation of neurodevelopmental and psychiatric conditions is common (9)(10)(11)(12). All RGDs studied to date affect cognition to varying degrees and affect a broad range of cognitive functions, including reaction time, attention, executive functions, and social cognition (13,14). Early studies highlighted distinctive behavioral profiles, such as social disinhibition, excessive empathy, and non-social anxiety described in 7q11.23 deletions (Williams-Beuren syndrome (15)); insatiable appetite in paternal 15q11.2-q13 deletions (Prader-Willi syndrome (16)); sleep disturbances in 17p11.2 deletions (Smith Magenis syndrome) (17); as well as childhood apraxia of speech in 16p11.2 proximal deletions (18).…”
Section: Do Rare Variants Exert Specific or Shared Effects On Psychop...mentioning
confidence: 99%
“…However, adding site as a covariate to the analyses generally did not alter results, except there was a significant difference between children and adolescents on working memory which was previously not significant. Furthermore, it is a strength that we have included adults, as there is far less research on older individuals than paediatric 22q11.2DS samples 31 .…”
Section: Limitationsmentioning
confidence: 99%
“…This may introduce bias as our comparisons for child and adolescence groups consisted of family controls. A meta-analysis reported that comparing the cognitive performance of individuals with 22q11.2DS to community controls produced smaller effect sizes than comparing against control siblings 31 . However, this did not appear to be the case in the current study, with effect sizes of a similar magnitude across developmental stages.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations